Multiple indicators yield diverging results on grazing degradation and climate controls across Tibetan pastures. (October 2018) - Wang, Yun; Lehnert, Lukas W.; Holzapfel, Maika; Schultz, Roland; Heberling, Gwendolyn; Görzen, Eugen; Meyer, Hanna; Seeber, Elke; Pinkert, Stefan; Ritz, Markus; Fu, Yao; Ansorge, Hermann; et al.
Highlights: Claims of grazing-caused degradation threat across Tibet pastures are exaggerated. Various indicators respond differently to grazing intensification. Climate controls were pronounced and overrode local grazing effects. Local abiotic conditions should be considered in grazing degradation assessments. Abstract: Understanding the impacts of livestock grazing is crucial to rangeland management and conservation. Numerous indicators have been employed to detect differences caused by grazing, while case studies suggest that effects differ among individual indicator systems. Across Tibetan pastures that have evolved with long grazing histories and harbour high levels of biodiversity, we tested: (1) whether commonly used grazing indicators differ in their sensitivity to grazing and environmental conditions, and (2) the relative importance of grazing and abiotic factors in controlling effects on indicators. Our sampling covered 18 sites within two main grassland types (steppe and meadow). We compared species compositions among communities of plants, small mammals and ants, as well as overall soil chemical conditions and field hyperspectral reflectance data using multivariate analyses between two qualitative levels of grazing intensity (heavy vs. light). Using univariate Generalized Linear Models, we explored the effects of grazing intensity, grassland type and their interaction on the richness and abundance of biotic groups as well as values of key soil and hyperspectral indices. The major environmental factors tested included temperature, precipitation, elevation, relief, exposure and inclination. Few of the indicators differed under relatively heavy grazing, including reductions in vegetation cover, soil organic carbon, total nitrogen concentration and two hyperspectral indices. Indicator groups differed both quantitatively and qualitatively with respect to grazing and climate impacts. Grazing effects were evident in the moist Kobresia meadows of eastern Tibet, while environmental controls dominated in alpine steppes of the drier western part of the plateau. Grazing effects on indicators thus depended on local precipitation conditions. Multivariate species compositions were affected by abiotic factors in all biotic indicator groups: precipitation was the most influential abiotic factor affecting plant species composition, overall soil nutrients and hyperspectral data, while elevation and temperature influenced ant and small mammal communities in terms of richness and species composition. Our results do not support the notion that local increases in relative grazing intensity have strong effects on the species richness of key biotic indicator groups across all Tibetan pastures. Reliable assessments of grazing effects thus require both multiple appropriate indicators and careful calibration to account for local climate and topographic conditions. Differences between principal grassland types must be acknowledged for future grassland conservation and management.